Rinse, Sense, Adjust, Repeat: Biomimetic Continuous Process Water Analysis in Washing Machines Based on the Hammerhead Shark's Olfaction Hydrodynamics. (3rd March 2020) - Kampowski, Tim; Langer, Max; Bold, Georg; Riffel, Michael; Ose, Lutz; Seidler, Christian; Schaumann, Uwe; Masselter, Tom; Speck, Thomas; Thielen, Marc
Abstract : Domestic household appliances (e.g., washing machines) are major factors in the anthropogenic global energy balance, which is why an efficient control of their energy and material consumption are of great importance in the future. At the same time, most of today's washing machines can be considered as "black boxes" which lack dynamic analysis techniques for an automated and optimized resource management. Following a biomimetic approach, rapid prototyping methods are combined with high‐speed videography and 2D particle tracking. In addition, preliminary work on the functional morphology and hydrodynamic characteristics of the olfactory organ of Sphyrna tudes is utilized to generate a flow channel module suitable for the implementation of diverse state‐of‐the‐art sensor technologies into innovative washing machines. The module's fluid dynamics are essentially determined by its optimized channel geometry and the fluid's inflow velocity. Future investigations will reveal whether a precise change of individual hydrodynamic parameters can solely be achieved by a variation of the inflow velocity and whether specific flow profiles can be established to allow for dynamic online analytics of multiple sensors during washing. Abstract : Energy and material consumption in washing machines can be reduced by optimizing and automatizing the consumption management. To this end, the integration of recent sensor technology is necessary, which often requires specific hydrodynamic characteristics. The olfactory organ of smalleye hammerhead sharks serves as a role model for the development and stepwise improvement for a flow channel module for washing machines.